2014
DOI: 10.1016/j.celrep.2014.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Sox4 Links Tumor Suppression to Accelerated Aging in Mice by Modulating Stem Cell Activation

Abstract: SummarySox4 expression is restricted in mammals to embryonic structures and some adult tissues, such as lymphoid organs, pancreas, intestine, and skin. During embryogenesis, Sox4 regulates mesenchymal and neural progenitor survival, as well as lymphocyte and myeloid differentiation, and contributes to pancreas, bone, and heart development. Aberrant Sox4 expression is linked to malignant transformation and metastasis in several types of cancer. To understand the role of Sox4 in the adult organism, we first gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 82 publications
3
37
0
Order By: Relevance
“…Mirroring the neuronal system (27), our studies established pancreatic SOX4 as a factor that initially specifies a terminally differentiated b-cell state (8) and then supports b-cell proliferation. This is in agreement with experimental evidence that SOX4 can act as an oncogene (28) as well as regulate cell-cycle genes and proliferation (29,30).…”
Section: Discussionsupporting
confidence: 92%
“…Mirroring the neuronal system (27), our studies established pancreatic SOX4 as a factor that initially specifies a terminally differentiated b-cell state (8) and then supports b-cell proliferation. This is in agreement with experimental evidence that SOX4 can act as an oncogene (28) as well as regulate cell-cycle genes and proliferation (29,30).…”
Section: Discussionsupporting
confidence: 92%
“…The promoter regions of the "late" period hubs are enriched in DNA binding motifs for E2F, ETS, GATA, the Wnt/β-catenin effectors (TCF/Myc), and Sox family proteins ( Figure 5A,B). These data are consistent with the downregulation of proliferation-related genes (E2F, ETS) ( Figures 2 and 3C,D), the acquisition of more differentiated and aging features (GATA, Sox, Wnt) [35][36][37][38] (Figure 4C), and the upregulation of Wnt/β-catenin gene signatures observed in our previous in silico analyses (Figure 3C,D; cluster "b"). However, given that the Myc gene signatures are downmodulated in this period (Figure 3C,D; cluster "f"), it is likely that the Wnt target genes could be regulated by either TCF proteins or other transcriptional factors working downstream of Wnt.…”
Section: Identification Of Transcriptional Factors Potentially Involvsupporting
confidence: 89%
“…In recent years, a number of studies have suggested that SOX4 may be associated with tumour development and progression (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%